2022
DOI: 10.1038/s41380-022-01515-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and the social facilitation of placebo effects

Abstract: Significant clinical improvement is often observed in patients who receive placebo treatment in randomized double-blind placebo-controlled trials. While a proportion of this “improvement” reflects experimental design limitations (e.g., reliance on subjective outcomes, unbalanced groups, reporting biases), some of it reflects genuine improvement corroborated by physiological change. Converging evidence across diverse medical conditions suggests that clinically-relevant benefits from placebo treatment are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 151 publications
0
13
0
Order By: Relevance
“…Previous studies have also highlighted the potential of placebobased responses to provide therapeutic outcomes across many clinical conditions [37][38][39] and also to moderate oxytocin based effects [19]. Meta-analyses in the autism field have further supported the existence of placebo responses of a moderate effect size [40].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have also highlighted the potential of placebobased responses to provide therapeutic outcomes across many clinical conditions [37][38][39] and also to moderate oxytocin based effects [19]. Meta-analyses in the autism field have further supported the existence of placebo responses of a moderate effect size [40].…”
Section: Discussionmentioning
confidence: 97%
“…These studies have, however, not been without controversy. Reviews of this evidence have highlighted the potential for placebo and expectancy effects to impact outcomes [14,18,19], a need for biological markers [13], a better understanding of drug delivery factors to inform use [20], and the role of early life development and social learning contexts [8], all of which might potentially moderate response [12]. To illustrate, the age of the child may play a part, with some evidence suggesting that younger children may show greater response to social interventions [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not explicitly addressed in the current study, it is also noteworthy to stipulate that the oxytocinergic system itself has been suggested to form a key mediator for facilitating placebo-induced improvements. Indeed, as postulated in the recent oxytocin-placebo account of Itskovich et al (2022); OT is suggested to mediate social facilitation of placebo effects, an effect that is thought to be facilitated by increased social connectedness between patient and clinician during trial participation. In line with this notion, a prior OT administration trial showed that placebo-induced improvements in social functioning coincided with endogenous increases in oxytocin secretion (Parker et al, 2017)…”
Section: Discussionmentioning
confidence: 99%
“…While not explicitly addressed in the current study, it is also noteworthy to stipulate that the oxytocinergic system itself has been suggested to form a key mediator for facilitating placebo-induced improvements. Indeed, as postulated in the recent oxytocin-placebo account of Itskovich et al (2022); OT is suggested to mediate social facilitation of placebo effects, an effect that is thought to be facilitated by increased social connectedness between patient and clinician during trial participation. In line with this notion, a prior OT administration trial showed that placebo-induced improvements in social functioning coincided with endogenous increases in oxytocin secretion (Parker et al, 2017) Further, in our trial, children who received the actual OT treatment in the first phase and crossed over to a second phase of active treatment, showed only non-significant withinsubject improvements from phase I to phase II, particularly at the four-week follow-up session of phase II -supporting prior observations of a retention of OT's beneficial effects, also after cessation of the daily nasal spray administrations (Alaerts et al, 2020;.…”
Section: Discussionmentioning
confidence: 99%